EFFICIENCY OF NOM REMOVAL AFTER COAGULATION-FILTRATION PROCESS USING FLUORESCENCE REGIONAL INTEGRATION METHOD - Okik Hendriyanto Cahyonugroho, Euis Nurul Hidayah, Yayok Suryo Purnomo (International Journal of Research Science and Management, 2016)
Natural organic matter (NOM) refers to group of carbon-based compounds that are found in surface water and ground water. The aim of the study is to determine the efficiency of coagulation-filtration process for removing NOM by using fluorescence spectra analysis. NOM surrogates, including total organic carbon (TOC), ultra violet absorbance at 254 nm (UV254), specific UV absorbance (SUVA), and fluorescence spectra analysis with Fluorescence integration method were chosen to assess the organic matter removal. Experiment was conducted by using activated carbon or silica sand as filter media under various flow rate after FeCl3 coagulation. Results revealed that activated carbon filter under lower flow rate rate showed better removal efficiency of NOM surrogates, around 40-60% and all fluorescence component, less than 40%, especially humic acid-like than silica filter media.